2024
DOI: 10.3390/ijms25074057
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles (AuNPs)—Toxicity, Safety and Green Synthesis: A Critical Review

Łukasz Niżnik,
Maciej Noga,
Damian Kobylarz
et al.

Abstract: In recent years, the extensive exploration of Gold Nanoparticles (AuNPs) has captivated the scientific community due to their versatile applications across various industries. With sizes typically ranging from 1 to 100 nm, AuNPs have emerged as promising entities for innovative technologies. This article comprehensively reviews recent advancements in AuNPs research, encompassing synthesis methodologies, diverse applications, and crucial insights into their toxicological profiles. Synthesis techniques for AuNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 227 publications
0
1
0
Order By: Relevance
“…Inorganic NPs may be a cause of inflammation in certain tissues . However, gold is generally considered a biocompatible and nontoxic material, although some studies have suggested the toxicity of AuNPs, especially at high concentrations. , To the best of our knowledge, no previous studies have found evidence of inflammation from direct intracranial administration of AuNPs. Our study did not thoroughly assess inflammation originating from the NP administration, but during the study period, no adverse effects were observed.…”
Section: Resultsmentioning
confidence: 93%
“…Inorganic NPs may be a cause of inflammation in certain tissues . However, gold is generally considered a biocompatible and nontoxic material, although some studies have suggested the toxicity of AuNPs, especially at high concentrations. , To the best of our knowledge, no previous studies have found evidence of inflammation from direct intracranial administration of AuNPs. Our study did not thoroughly assess inflammation originating from the NP administration, but during the study period, no adverse effects were observed.…”
Section: Resultsmentioning
confidence: 93%